Second pregnancy following kidney transplantation is not associated with an increased risk of graft loss in a single center retrospective cohort study. Issue 8 (14th June 2022) - Lichtenberg, Shelly; Freilich Rom, Dana; Aspitz, Haggar Zoe; Keshet, Rom; Rahamimov, Ruth; Rozen‐Zvi, Benaya
Abstract: Introduction: Previous studies on first pregnancy following kidney transplantation (KT) show no association with decreased graft survival. This study examined patients with multiple gestations compared to a single pregnancy following KT and evaluated the risk of graft function deterioration. Methods: A retrospective cohort study on fertile female kidney transplant recipients (KTRs) from Rabin Medical Center between January 2001 and December 2017 was performed. Data were collected on patients' comorbidities, pregnancy complications, graft loss, mortality, and lab results. Time‐varying COX analysis was performed ‐ second pregnancy being the time‐related variable. Results: Fifty‐two KTRs split into 30 single pregnancy and 22 multiple pregnancy patients following KT. Single pregnancy patients were older during their first pregnancy and had a higher caesarian section rate. During a median follow‐up period of 5.6 years, multiple pregnancies, compared to a single pregnancy, were not associated with an increased rate of graft loss. No significant difference was seen between first and second pregnancy in gestational age, birth weight, graft function, and proteinuria rates. Conclusions: Second pregnancy following KT was not shown to be associated with a decreased graft survival. In addition, obstetrical, maternal, and fetal complication rates are not increased in second compared to first pregnancy following KT.